2014
DOI: 10.1021/nl501753n
|View full text |Cite
|
Sign up to set email alerts
|

Unzipping Carbon Nanotubes at High Impact

Abstract: The way nanostructures behave and mechanically respond to high impact collision is a topic of intrigue. For anisotropic nanostructures, such as carbon nanotubes, this response will be complicated based on the impact geometry. Here we report the result of hypervelocity impact of nanotubes against solid targets and show that impact produces a large number of defects in the nanotubes, as well as rapid atom evaporation, leading to their unzipping along the nanotube axis. Fully atomistic reactive molecular dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 20 publications
3
81
0
Order By: Relevance
“…26b). This is consistent with the finding that high impact can unzip carbon nanotubes (Ozden et al 2014). Chew et al (2011) found that the com- Fig.…”
Section: With Permissionsupporting
confidence: 89%
“…26b). This is consistent with the finding that high impact can unzip carbon nanotubes (Ozden et al 2014). Chew et al (2011) found that the com- Fig.…”
Section: With Permissionsupporting
confidence: 89%
“…Jiao et al and Kosynkin et al successfully employed this technique for the first time to prepare graphene nanosheets from MWCNTs 37,38 . Since then, many reports have appeared on the preparation of graphene nanosheets from MWCNTs [39][40][41][42][43] . Besides chemical unzipping, plasma, microwave, electrochemical, microwave and laser assisted unzipping methods have all been used to prepare graphene nanosheets [44][45][46][47] .…”
Section: Introductionmentioning
confidence: 99%
“…In such kind of complex processes, the fracturing of C-C bonds along a particular direction needs high energy, which can be provided using high strain rate (10 8À10 /s) deformation [20][21][22][23]. In our previous work, we reported a combined experimental and theoretical study of CNTs under high velocity impact [24]. Such experiments give rise to one step chemical-free unzipping due to local concentration of stress at particular location of CNT [24].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we reported a combined experimental and theoretical study of CNTs under high velocity impact [24]. Such experiments give rise to one step chemical-free unzipping due to local concentration of stress at particular location of CNT [24]. Utilising this understanding, we used a cryo-milling machine designed by us (KC0, Tau Instrument, Bangalore, India) that can deform CNTs with a frequency of 50 Hz and displacement amplitude of 3 mm of the vibrating ball.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation